Comparison of Endogenous Endophthalmitis in Patients with and Without COVID-19 Infection - Ehsan Namvar; Mehdi Moallem; Mehrdad Afarid; Alireza Bolkheir (Journal of Ophthalmology)
Introduction. Endogenous endophthalmitis (EE) is an ophthalmic emergency that can have severe sight-threatening complications. Prompt diagnosis and aggressive treatment are central to the successful management of EE. In recent years, a significant increase has occurred in the number of cases of EE. Some of these individuals had a COVID-19 infection. The current study compared EE in patients with and without COVID-19 infection. Methods. All cases of EE admitted to Khalili Hospital between April 2020 and September 2021 were included in this prospective case-control study. Patients were divided into 2 groups: (i) the case group (EE patients with confirmed COVID-19 infection; n = 7) and (ii) the control group (EE patients without a history or evidence of COVID-19 infection; n = 7). Age, sex, presenting and final visual acuity, systemic diseases and risk factors for EE, anterior segment and fundus findings, hospitalization due to COVID-19, intensive care unit (ICU) admission, systemic steroid therapy, results of the sepsis workup, causative microorganism, types of treatment (pars plana vitrectomy vs. intravitreal or antifungal antibiotics), and follow-up period were recorded. Results. Twenty-four eyes of the 14 patients were included in this study, of which 9 were female. The mean age was 49.57 years. Follow-ups ranged from 1 month to 20 months (mean, 8 months). There were no statistically significant differences in age (P = 0.653), mean follow-up (P = 0.943), gender (P = 0.313), and clinical presentation (P = 0.409) between the case and control groups. Seven patients (50%) had positive intraocular culture results. Two out of 7 patients had a history of COVID-19 infection. The most common causative microorganism was Candida (4 patients [28.57%]; 6 eyes [25%]). No statistically significant differences were observed between the 2 groups in the need for vitrectomy (P = 1.000). The visual outcome between the 2 groups was similar (P = 0.179). Conclusion. The COVID-19 infection does not seem to affect the severity, visual outcomes, improvement rate, or vitrectomy rate of EE. Early diagnosis and management, especially pars plana vitrectomy, can prevent serious complications and save many eyes.